2016
DOI: 10.3390/ijerph13111078
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Mutagenicity and Heavy Metal Concentrations of Leachates Extracted from the Fly and Bottom Ash Derived from Municipal Solid Waste Incineration

Abstract: Two incinerators in Taiwan have recently attempted to reuse the fly and bottom ash that they produce, but the mutagenicity of these types of ash has not yet been assessed. Therefore, we evaluated the mutagenicity of the ash with the Ames mutagenicity assay using the TA98, TA100, and TA1535 bacterial strains. We obtained three leachates from three leachants of varying pH values using the toxicity characteristic leaching procedure test recommended by the Taiwan Environmental Protection Agency (Taiwan EPA). We th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Our investigations showed that ashes produced from thermally unconverted biomass had higher leachability of heavy metals. [3,11,58]. On the other hand, taking into account regulatory limits (2003/33/EC), the not-hazardous limits for leachates for Cr, Ni, Cd, and Pb are: 4 mg, 5 mg, 0.6 mg, and 5 mg/ kg, respectively.…”
Section: Leachability Ph and Ec Of Heavy Metals In Biomass Ashmentioning
confidence: 99%
See 2 more Smart Citations
“…Our investigations showed that ashes produced from thermally unconverted biomass had higher leachability of heavy metals. [3,11,58]. On the other hand, taking into account regulatory limits (2003/33/EC), the not-hazardous limits for leachates for Cr, Ni, Cd, and Pb are: 4 mg, 5 mg, 0.6 mg, and 5 mg/ kg, respectively.…”
Section: Leachability Ph and Ec Of Heavy Metals In Biomass Ashmentioning
confidence: 99%
“…Nowadays, biomass is considered one of the most promising sources of the renewable energy, especially in the case of small-scale boilers used for municipal heating. It is worth mentioning that biomass is also widely used in the production of electricity and district heat, reducing the emission of carbon dioxide [1][2][3][4]. The worldwide technological development accompanied by a continuous increase of energy consumption as well as the need to implement provisions of the Kyoto Protocol cause a steadily increasing interest in the use of energy from renewable sources [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few papers, for example, have suggested that, though the TCLP leaching concentrations of heavy metals from cyclone ash, scrubber ash, and bottom ash met relevant regulations, their leachates still showed evident biotoxicity toward experimental subjects such as Escherichia coli DH5, Bacillus subtilis , wheat seeds, etc. [ 10 , 11 , 12 , 13 ]. Furthermore, fly ash would suffer a high-temperature thermal process when it was reutilized as an alternative to some mineral materials for producing construction materials such as ceramic bricks.…”
Section: Introductionmentioning
confidence: 99%
“…ESPs have been industrially used to eliminate polluting particles in gases since the beginning of the 20th century [1][2][3][4]. They are durable, relatively simple to maintain, cost-effective and present a high collection efficiency, typically 80% per step.…”
Section: Introductionmentioning
confidence: 99%